2022
DOI: 10.1155/2022/2085267
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Immunotherapy Improves Treatment for Early Resectable Non-Small-Cell Lung Cancer: A Systematic Review and Meta-analysis

Abstract: Objective. Immunotherapy has shown better efficacy and less toxicity than chemotherapy in the treatment of non-small-cell lung cancer (NSCLC) at advanced stage. This study evaluates the safety and efficacy of neoadjuvant immunotherapy for resectable NSCLC. Methods. Literature examination was performed by searching the PubMed, the Cochrane Library, and Embase for articles evaluating the efficacy and safety of neoadjuvant immunotherapy for resectable NSCLC. The 95% confidence interval (CI) and effect sizes (ES) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…It cannot be excluded that the differences are related to indicators such as the neoadjuvant treatment regimen, cycle, or type of immune checkpoint inhibitors (ICIs). Previous meta-analyses have confirmed that different ICIs have no significant impact on the safety and feasibility of treatment (7). Therefore, we conducted a meta-analysis of the different neoadjuvant immunotherapy regimens and cycles.…”
Section: Introductionmentioning
confidence: 98%
“…It cannot be excluded that the differences are related to indicators such as the neoadjuvant treatment regimen, cycle, or type of immune checkpoint inhibitors (ICIs). Previous meta-analyses have confirmed that different ICIs have no significant impact on the safety and feasibility of treatment (7). Therefore, we conducted a meta-analysis of the different neoadjuvant immunotherapy regimens and cycles.…”
Section: Introductionmentioning
confidence: 98%
“…Through a previous literature search, we found that the current systematic reviews and meta-analyses [10][11][12][13][14][15][16][17] of neoadjuvant immunotherapy in NSCLC were just based on singlearm studies, or single-arm and multiarm mixed studies, but not based on RCTs. In this study, a systematic review and metaanalysis were conducted based on the RCTs (Supplemental Materials, Table S1, Supplemental Digital Content 1, http:// links.lww.com/AJCO/A493; "Preferred Reporting Items for Systematic Reviews and Meta-analyses" checklist) to evaluate the efficacy and safety of neoadjuvant immunotherapy for NSCLC, to provide more reliable clinical evidence for neoadjuvant immunotherapy of patients with NSCLC.…”
mentioning
confidence: 99%